Students Experiences in Using E-Books As A Learning Resource - Riri Zaniah Laksono; Asep Hardiyanto (Universitas Islam Negeri Palopo, 2025)
E-books have emerged as an important learning tool that supplements traditional resources, and rapid technological advancements have brought about significant changes in education. Because they provide widespread and early access, e-books are an essential way to meet the demands of 21st-century skills. Despite the effectiveness and technological challenges of e-books, there is a study shortage addressing in-depth qualitative investigation of students' subjective experiences in the learning context. In order to create a more effective curriculum, this study aims to ascertain students' experiences, emotions, and use of e-books in the learning process. 36 grade XI 7 students from SMA Negeri 2 Kotabumi participated in this study, which employed a qualitative descriptive method. A single tool, a 12-item open-ended questionnaire, was used to gather the data, which were then subjected to qualitative systematic content analysis techniques. The findings indicate that students' experiences are dualistic. Many had positive experiences: e-books considerably helped conceptual understanding, offered simple access, mobility, and cost-effectiveness, and delivered enhanced academic performance. On the other hand, this experience is offset by significant challenges, namely distractions from other app notifications (resulting in loss of focus), visual fatigue, and technical constraints (signal/battery). This paradox shows that comfortable learning is not always ensured by digital efficiency. E-books are a vital tool in the digital age and efficiently facilitate self-directed learning. To ensure a balanced and ideal learning experience, however, environmental challenges necessitate that educators and schools adopt digital policies that reduce distractions and incorporate e-books as an enrichment resource rather than a total replacement.